Korelasi Pengembangan Nilai Karaker Pendidikan Kepramukaan dengan Pembelajaran Pendidikan Agama Islam - Royani; Dede Supendi (Paedagogie: Jurnal Pendidikan dan studi Islam, 2023)
In the world of education these days, things related to the phenomenon of moral decadence that occur in the midst of society and in the government environment are increasing and diverse. Scouting Education and Islamic Religious Education are expected to be able to produce human beings who always strive to perfect faith, piety, and noble character, noble morals include ethics, ethics, or morals as the embodiment of education. Such human beings are expected to be resilient in facing challenges, obstacles, and changes that arise in community associations both locally, nationally, regionally and globally. Scouting Education is a non-formal education in which there is a process of forming the personality, life skills, and noble morals of scouts through the passion and practice of scouting values for students in the Education Unit is a School. Islamic Religious Education is an education that provides knowledge and shapes the attitudes, personalities and skills of students in practicing the teachings of the Islamic religion, which is carried out at least through subjects at all levels of education.